Introduction to Canadian studies from Nordic and Baltic perspectives - Christophe Premat (2021)
This presentation is a part of a course at the basic level at Stockholm University. It is a course which was supported by the Centre for Canadian Studies of Stockholm University. The course is designed to introduce students to a variety of aspects related to the history, culture and literature of Canadian society. It also tackles the bilingual aspect of Canadian society and helps students to discuss issues that are relevant in Canada. The course then looks at the challenges facing Canada in the 21st Century with focus on immigration and multiculturalism, the First Nations, gender equality, specific regions in Canada with special emphasis on Québec, and Canada's cultural identity. The introduction focuses on the historical and political aspects of Canada. It also borrows the concept of “politics of recognition” to understand the relations between two former colonial powers and indigenous populations.